URBAN AGRICULTURE BERBASIS THIRD PLACE DI BENDUNGAN HILIR, JAKARTA PUSAT - Meidiana, Jessica; Hadiwono, Alvin (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2025)
According to data from the Central Bureau of Statistics (BPS) in 2023, Indonesia is facing a decline in food supply due to a crisis in the regeneration of young farmers. This issue is driven by the negative stigma towards agriculture, which is often considered dirty, high-risk, and less prestigious. As a result, many young people are more attracted to urbanisation. Therefore, efforts are needed to revive the interest of the younger generation in farming activities by developing the third place concept based on locality, which can be described as the informal space between home and work where people can relax. This agricultural project invites visitors to practice and observe the entire farming process from start to finish. Supported by a programme that utilizes the concept itself, such as Co-Working space, Communal Space, Mini Plaza, dan Garden Terrace. By utilising the everydayness approaches, this urban farming project encourages the community to carry out routine activities such as planting seeds, harvesting, and carrying the crops to plant them at home. As a result, this project is expected to serve as a temporary gathering place (third place) for the community, especially young people, to enjoy traditional farming activities and incorporate modern techniques such as hydroponics, aquaponics, and aeroponics to create a new lifestyle for achieving food security district. Thus, this project acts as a locus to secure the food system but also to increase the quality of third place in the community’s everydayness through social interaction and improving well-being. Keywords: urban agriculture; locality; third place; everydayness; regenerative; locus Abstrak Berdasarkan sumber dari Badan Pusat Statistik di tahun 2023, Indonesia sedang menghadapi permasalahan penurunan pasokan pangan. Hal ini disebabkan oleh krisis regenerasi petani muda yang didorong dengan munculnya stigma negatif akan dunia pertanian yang dianggap kotor, tinggi resiko, dan kurang bergengsi sehingga kaum muda lebih tertarik untuk melakukan gerakan urbanisasi. Oleh karena ini diperlukannya upaya untuk memunculkan kembali minat bagi kaum generasi muda dalam kegiatan bertani melalui pengembangan konsep Third Place berbasis lokalitas yang diartikan sebagai ruang sosial informal antara rumah dan pekerjaan yang dimana orang-orang bisa bersantai. Proyek agrikultur ini mengajak pengunjung untuk mempraktekkan dan melihat prosesi pertanian dari awal hingga akhir. Dengan hadirnya program penunjang yang menciptakan interaksi sosial berupa Co-Working space, Communal Space, Mini Plaza, dan Garden Terrace. Dengan memanfaatkan pendekatan everydayness, proyek Urban Agriculture ini mendorong munculnya budaya akan aktivitas masyarakat yang baru seperti menanam bibit, memanen hasil dan merawat hasilnya. Dengan itu, diharapkan proyek ini bisa dijadikan sebagai tempat rekreasi untuk masyarakat khususnya kaum muda untuk menikmati kegiatan bertani yang tidak hanya tradisional, namun juga ada teknik hidroponik, akuaponik, dan juga aeroponik guna membentuk gaya hidup baru untuk mencipatakan kawasan yang mandiri pangan. Sehingga, proyek berperan sebagai locus segi ketahanan pangan tapi juga memperkuat kualitas third place dalam keseharian masyarakat melalui interaksi sosial melalui komunitas dan peningkatan kualitas hidup.